Efektivitas Kitosan dan Ekstrak Daun Abelmoschus dalam Mengurangi Nilai COD, BOD, dan Logam Berat pada Limbah Laboratorium Kimia - Hana Rohana; Zakiah Dzulummah; Cahyo Puji Asmoro (Jurnal Pengelolaan Laboratorium Pendidikan, 2026)
Chemical laboratory wastewater is classified as hazardous due to the presence of compounds that can pose serious risks to both human health and the surrounding environment. Parameters such as Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), and heavy metal content serve as key indicators of water pollution, reflecting its quality and environmental impact. In this study, treatment of complex chemical laboratory wastewater was carried out through coagulation and flocculation processes using natural coagulants derived from chitosan and Abelmoschus leaf extract. The main objective of this research was to evaluate the effectiveness of these organic coagulants in reducing COD, BOD, and heavy metal concentrations. The experiment consisted of two stages: (1) optimization of treatment parameters using the Jar Test method, and (2) analysis of treated and untreated wastewater for COD, BOD, and heavy metals (Cr, Mn, Cu, Pb, Zn, Ni, and Fe) using Atomic Absorption Spectrophotometry (AAS). The results revealed that the treatment successfully reduced COD from 74,928 mg/L to 65,311 mg/L; Cr from 3.422 mg/L to 2.877 mg/L; Mn from 5.084 mg/L to 4.787 mg/L; Cu from 36.548 mg/L to 9.902 mg/L; Pb from 0.169 mg/L to 0.141 mg/L; Zn from 0.342 mg/L to 0.243 mg/L; Ni from 23.79 mg/L to 17.375 mg/L; and Fe from 13.615 mg/L to 7.697 mg/L. However, the BOD value increased from 383 mg/L to 453.5 mg/L, which is likely due to the introduction of organic matter from the natural coagulants and flocculants used. For improved treatment efficiency, further processes such as filtration or adsorption using activated carbon, zeolite, or bentonite, as well as biological treatment with activated sludge, are recommended..